Spatiotemporal characteristics and attribution of dry/wet conditions in the Weihe River Basin within a typical monsoon transition zone of East Asia over the recent 547 years. (September 2021) - Chen, Xinyu; Quan, Quan; Zhang, Ke; Wei, Jiahua
Abstract: The Weihe River Basin (WRB) in a monsoon transition zone of East Asia interacts with multiple weather systems and is susceptible to floods and droughts. We developed a framework based on the Empirical Orthogonal Function analysis, Complete Ensemble Empirical Mode Decomposition with Adaptive Noise analysis, and moving-average based Spearman rank correlation to identify the spatial patterns of the dry/wet conditions from 1470 to 2016, decompose the dry/wet index into the leading components with a period between 2 and 3 years and 100+ years, and discover their driving forces on multiple time scales. Results show that WRB can be divided into four distinguishable hydroclimatic subregions located in the southeast, west, central, and north. The East Asian summer monsoon and South Asian summer monsoon impact this region mainly on the inter-annual and inter-decadal scales, while the impacts of ENSO, PDO, AO, and NAO are dominant on the multi-decadal and centennial scales. Graphical abstract: Image 1 Highlights: Developed a new framework to attribute dry/wet spatiotemporal variability on multiple time scales. Revealed four unique hydroclimatic subregions for the Weihe River Basin. Identified the effects of monsoons, plateau circulation, westerly, and solar activities on Weihe. Dry/wet conditions of the subregions show opposite responses to solar activity.